Pengaruh Promosi Jabatan, Kompensasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Perhubungan Kota Malang - Putri Nataliasari; Ronny Malavia Mardani; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this research is to determine the effect of job promotion, compensation and work discipline on the performance of employees of the Transportation Department of Malang City. The data source of this research is primary data obtained from answers to questions when distributing questionnaires to employees of the transportation department. The sample method used is saturated sample. The number of samples in this research was 98 respondents. Data analysis methods using multiple linear regression analysis with classical assumption tests and statistical tests. The results showed: (1) job promotion has a significant effect on employee performance, (2) compensation has no significant effect on employee performance, (3) work discipline has no significant effect on employee performance. Keywords: Job Promotion, Compensation, Work Discipline